The challenge of legislation bipartisanship in a partisan world - Hilley, John L. (Brookings Institution Press, 2008)
"Insider's account of the bipartisan passage of the Balanced Budget Act of 1997. Weaves together detailed narrative and portraits of key players and offers unique insight into the relationship between party leaders and their rank-and-file, the interplay between elected officials and their staff, and the delicate art of partisan negotiations"--Provided by publisher.